An audit of the management of threatened preterm labour. (16th November 2010) - Owen, R; Bird, A; Candelier, CK
Abstract : Preterm birth has an incidence of around 5–8%, however more women will present with symptoms or signs of preterm labour and predicting which of these women will go on to deliver prematurely can be difficult. The authors performed an audit in our unit to examine the proportion of women presenting with threatened preterm labour and how these women were managed. At the time of the audit, the fetal fibronectin test was not in use. In 1 month, almost 20% of admissions were with symptoms or signs of threatened preterm labour. Most of these women are managed by administering steroids and tocolysis if indicated and in a small number of patients, an in-utero transfer to another unit is necessary. In-utero transfer has a large cost implication, not to mention the social upheaval for the woman and her family and the effects on workload for the receiving unit. A recent Fibronectin pilot study performed across Greater Manchester has suggested that the use of Fibronectin testing for women who present in threatened preterm labour may prevent around 15% of in-utero transfers. The authors plan to use the results of our audit to provide us with a cost saving estimate upon the introduction of fibronectin testing which is planned for later this year. The authors will then reaudit once fibronectin is in use to demonstrate the cost effectiveness of this test and the way it can improve the maternity service for women.